BE CAREFUL WHAT YOU ASK FOR: WHEN BASIC WRITERS TAKE THE RHETORICAL STAGE - Biser, Eileen and Rubel, Linda and Toscano, Rose Marie (Journal of Basic Writing, 2002)
An implicit part of a writing teacher's purpose is to help students find a public voice through writing, encouraging them to become rhetors who take public and enact change. Although risk is inherent in any public rhetorical act, when basic writers address those in the mainstream, the risks intensify. These students are challenged not only by the rigors of writing within traditional forms, but also by the burden of persuading from '' without" This essay examines the challenges one basic writer, a deaf student at the Rochester Institute of Technology, confronted when she took on the role of public writer. This student's attempt to enact change is analyzed for the sake of uncovering the pedagogical implications that teachers of basic writing must consider when educating students to write for the public sphere.
https://katalog.adlr.link/Record/ai-55-aHR0cHM6Ly93d3cuanN0b3Iub3JnL3N0YWJsZS80MzQ0NDA1OA